HOW THE TYPE OF OWNERSHIP AFFECTS CAPITAL BUDGETING PRACTICE IN THE SERBIAN AGRIBUSINESS INDUSTRY? - Barjaktarovic, Lidija Dragoljub; Pindzo, Renata; Konjikušić, Snezana (Economics of Agriculture, 2020)
The subject of the research is capital budgeting practices in Serbian agribusiness companies. The research aim is to determine whether there are differences in decision-making regarding capital budgeting depending on the ownership structure in those industries. The research was conducted in the first half of 2019, on a sample of 76 companies (from 122 targeted/i.e. 62.33% respondent rate) operating in the Republic of Serbia. Descriptive statistics and the Kruskal Wallis test were used in the data analysis. IBM SPSS 20.0 statistical package was used for data processing. Research results confirmed that capital budgeting practices in the Serbian agribusiness companies can be considered as developed. Furthermore, there is a difference in the capital budgeting practices in the Republic of Serbia depending on the ownership of the analyzed sampled companies.